A Model of the Effects of Reputational Rankings on Organizational Change - Martins, Luis L. (Organization Science, 2005)
Reputational rankings published by the media have emerged as important sources of institutional isomorphic pressures on organizations. However, organizations vary in the extent to which they respond to the pressures exerted by the rankings, and research to date has not examined why some organizations change in response to the rankings and others do not. This study develops and tests a model that examines how top managers’ sensemaking of rankings affects organizational change. Specifically, the model proposes direct and moderated effects of a perceived discrepancy between the position assigned to an organization in the rankings and the position implied by the organization’s identity in the minds of its top managers (referred to here as a “perceived identity-reputation discrepancy”), on the extent of change undertaken by the organization. The research context used for the study was U.S. graduate schools of business. The results show that, as expected, schools whose top managers believed that their rankings were discrepant from their own perceptions of their school’s standing in the industry, were more likely to undertake organizational change. This relationship was moderated by top managers’ perceptions of the strategic impact of the rankings, and by the strength and external orientation of organizational identity; the relationship was not moderated by the perceived validity of the rankings. Overall, the results suggest that managerial interpretations and organizational identity work in concert to explain variation across organizations in the extent to which rankings motivate organizational change.